Diversity and Inclusion in Conservation: A Proposal for a Marine Diversity Network - Smith, Nicola S.; Côté, Isabelle M.; Martinez-Estevez, Lourdes; Hind-Ozan, Edward J.; Quiros, Angela L.; Johnson, Nathan; Green, Stephanie J.; Cornick, Leslie; Shiffman, David; Malpica-Cruz, Luis; Gleason Besch, Allison; Shiel-Rolle, Nikita (Frontiers in Marine Science, 2017)
NA